A dynamic model of a 100 kW micro gas turbine fuelled with natural gas and hydrogen blends and its application in a hybrid energy grid. (15th June 2017) - di Gaeta, Alessandro; Reale, Fabrizio; Chiariello, Fabio; Massoli, Patrizio
Abstract: The paper deals with the development of a dynamic model of a commercial 100 kW Micro Gas Turbine (MGT) fuelled with mixtures of standard (i.e. natural gas or methane) and alternative fuels (i.e. hydrogen). The model consists of a first-order differential equation (ODE) describing the dominant dynamics of the MGT imposed by its own control system during production electrical power. The differential equation is coupled to a set of nonlinear maps derived numerically from a detailed 0D thermodynamic matching model of the MGT evaluated over a wide range of operating conditions (i.e. mechanical power, fraction of hydrogen and ambient temperature). The efficiency of the electrical machine with power inverter and power absorbed by auxiliary devices is also taken into account. The resulting model is experimentally validated for a sequence of power step responses of the MGT at different ambient conditions and with different fuel mixtures. The model is suited for simulation and control of hybrid energy grids (HEGs) which rely on advanced use of MGT and hydrogen as energy carrier. In this regard, the MGT model is used in the simulation of an HEG based on an appropriate mix of renewable (non-programmable) and non-renewable (programmable) energy sources with hydrogen storage and its reuse in the MGT. Here, the MGT is used as a programmable energy vector for compensating the deficits of renewable energies (such as solar and wind ) with respect to user demand, while excess renewable energy is used to produce hydrogen via electrolysis of water. The simulated HEG comprises a solar PhotoVoltaic (PV) plant (300 kW), an MGT (100 kW) fuelled with natural gas and hydrogen blends, a water electrolyzer (WE) system (8 bar, 56 Nm 3 /h), a hydrogen tank (54 m 3 ), and an Energy Management Control System (EMCS). Highlights: A dynamic model of a commercial 100 kW MGT fuelled with natural gas and hydrogen blends is developed. The model reproduces the electrical power generated by the MGT in steady and transient conditions. The MGT model enables simulation of hybrid energy grids based on a mix of renewables, hydrogen storage and its reuse in MGT. The MGT coupled with a water electrolyzer (WE) can be used for making more programmable the nonprogrammable renewable sources. Hybrid energy grid comprising the MGT, a WE, a PV and a hydrogen tank is simulated on a period of one year.